Immunogenicity of the meningococcal stress protein MSP63 during natural infection. - Pannekoek, Y (1993)
Acute- and convalescent-phase sera from 40 patients with meningococcal disease were evaluated for immunoreactivity with the meningococcal member of the hsp60 stress protein family. The IgG response was measured by ELISA, using bacterial cell lysate of the corresponding patients' strain, and purified hsp60 proteins from Neisseria meningitidis (MSP63), Escherichia coli (GroEL) and Mycobacterium bovis BCG (65K) as antigens. Analysis of the antibody responses revealed that 24/35 patients (69%) with elevated anti-meningococcal titres, generated anti-MSP63 antibodies during the time course of infection. Twelve of these patients generated antibodies specific for MSP63, in six patients anti-MSP63 levels exceeded anti-GroEL/65K antibodies. In the remaining six patients, equal levels of anti-MSP63 and anti-GroEL/65K were measured. We conclude that MSP63 is expressed and immunogenic during natural meningococcal infection, and that individual subjects have a restricted response to the antigen, resulting in the recognition of Neisseria-specific hsp60 epitopes and/or cross-reactive hsp60 determinants.